Strategi Peningkatan Kualitas Akuntabilitas Kinerja Studi Kasus: Implementasi SAKIP di Kabupaten Bogor - Alfiana, Rizki Putra; Asropi, Asropi; Rusliandi, Rusliandi (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the strategy for improving the quality of performance accountability in the Bogor Regency Government through the public accountability approach by Bovens (2007) and the GRIT strategy introduced by Duckworth (2016). Although there have been advancements in implementing electronic-based planning, reporting, and evaluation systems, SAKIP evaluation results indicate performance stagnation in recent years. A qualitative approach was used with a case study method and data collected through in-depth interviews with key actors managing performance. The study findings show that reporting and evaluation aspects have not been fully utilized as a basis for decision-making. The strategy implemented by the Bogor Regency Government contains elements of GRIT: the courage to initiate breakthroughs, resilience in facing limitations, initiative in making improvements, and perseverance in maintaining coordination rhythms. However, this spirit has not yet fully become an organizational culture. Therefore, it is necessary to optimize accountability forums, strengthen objective reward and punishment systems, and systematically internalize GRIT values across all regional apparatuses.